Effects of whole-body Adenylyl cyclase 5 (Adcy5) deficiency on systemic insulin sensitivity and adipose tissue - Dommel, Sebastian; Hoffmann, Anne; Berger, Claudia; Kern, Matthias; Klöting-Blüher, Nora; Kannt, Aimo; Blüher, Matthias (International journal of molecular sciences, 2021)
Genome-wide association studies have identified adenylyl cyclase type 5 (ADCY5) as candidate gene for diabetes-related quantitative traits and an increased risk of type 2 diabetes. Mice with a whole-body deletion of Adcy5 (Adcy5-/-) do not develop obesity, glucose intolerance and insulin resistance, have improved cardiac function and increased longevity. Here, we investigated Adcy5 knockout mice (Adcy5-/-) to test the hypothesis that changes in adipose tissue (AT) may contribute to the reported healthier phenotype. In contrast to previous reports, we found that deletion of Adcy5 did not confer any physiological or biochemical benefits. However, this unexpected finding allowed us to investigate the effects of Adcy5 depletion on AT independently of lower body weight and a metabolically healthier phenotype. Adcy5-/- mice exhibited an increased number of smaller adipocytes, lower mean adipocyte size and a distinct AT gene expression pattern with midline 1 (Mid1) as the most significantly downregulated gene compared to control mice. Our Adcy5-/- model challenges previously described beneficial effects of Adcy5 deficiency and suggests that targeting Adcy5 does not improve insulin sensitivity and may therefore limit the relevance of ADCY5 as potential drug target.
Gesehen am 11.11.2021